Penggunaan Tanaman Obat Tradisional Untuk Meningkatkan Nafsu Makan Pada Balita - Ari Kurniarum; Rizky Ayu Novitasari (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Use of Traditional Medicinal Plants, Appetite, Toddler. Causes of malnutrition in children under five is no appetite, then the parents use alternative to traditional medicinal plants. The purpose of this study was fatherly to know the use of traditional medicinal plants to improve appetite in infants. Quantitative descriptive research study subjects were women who use traditional medicinal plants to improve appetite in infants by 36 samples. The statistical test used this research is descriptive test. The results showed that the majority of children experiencing increasing appetite after the use of traditional medicinal plants.